2019
DOI: 10.1186/s12882-019-1308-z
|View full text |Cite
|
Sign up to set email alerts
|

IL17A and IL17F genes polymorphisms are associated with histopathological changes in transplanted kidney

Abstract: Background Interleukin 17 is a proinflammatory cytokine involved in immune response after allograft transplantation. IL-17 family of proinflammatory cytokines includes IL-17A and IL-17F . Previous studies have demonstrated that the rs2275913 IL17A and the rs11465553 IL17F gene polymorphism are associated with kidney allograft function. Because of the association between these polymorphisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…(22), since in the present study, no significant association between NODAT and CC and TC genotypes was seen. In previous studies, the C17 allele of the IL-17F rs76378 gene polymorphism was associated with high concentrations of long-term creatinine and high severity of tubular atrophy and interstitial fibrosis were reported (21). However, in the present study, no significant difference was observed between the distribution of genotypes of the IL-17F T/C (rs763780) and the amount of creatinine and FBS three months and six months after transplantation.…”
Section: Zununi Vahed S Et Alcontrasting
confidence: 81%
See 1 more Smart Citation
“…(22), since in the present study, no significant association between NODAT and CC and TC genotypes was seen. In previous studies, the C17 allele of the IL-17F rs76378 gene polymorphism was associated with high concentrations of long-term creatinine and high severity of tubular atrophy and interstitial fibrosis were reported (21). However, in the present study, no significant difference was observed between the distribution of genotypes of the IL-17F T/C (rs763780) and the amount of creatinine and FBS three months and six months after transplantation.…”
Section: Zununi Vahed S Et Alcontrasting
confidence: 81%
“…IL-17F gene SNP 7489A/G is linked with graft failure (20). Moreover, the association of IL-17A rs2275913 gene polymorphism with histopathological changes of kidney allograft (21) and its association (rs2275913 GG) with an increased risk of delayed graft function and higher serum creatinine have been reported (22). The GA genotype of the IL-17F gene polymorphism (rs11465553) might be associated with a high risk of transplanted renal function and return to dialysis after kidney transplantation (22).…”
Section: Zununi Vahed S Et Almentioning
confidence: 99%
“…Common polymorphisms in the IL-17A gene have been associated with hypertension [ 31 ] and various organ dysfunctions [ 32 ]. As the primary clinical characteristics of PE are high blood pressure and dysfunction of kidney and liver, we hypothesized that variants in the IL-17A gene would be associated with predisposition to the development of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Common polymorphisms in the IL-17A gene have been associated with hypertension (Huang et al 2017)and various organ dysfunctions (Domanski et al 2019). As the primary clinical characteristics of PE are high blood pressure and dysfunction of kidney and liver, we hypothesized that variants in the IL-17A gene would be associated with predisposition to the development of PE.…”
Section: Discussionmentioning
confidence: 99%